If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(x + -1) + -1(5x + -6) = 3(4x + -1) + -8 Reorder the terms: 4(-1 + x) + -1(5x + -6) = 3(4x + -1) + -8 (-1 * 4 + x * 4) + -1(5x + -6) = 3(4x + -1) + -8 (-4 + 4x) + -1(5x + -6) = 3(4x + -1) + -8 Reorder the terms: -4 + 4x + -1(-6 + 5x) = 3(4x + -1) + -8 -4 + 4x + (-6 * -1 + 5x * -1) = 3(4x + -1) + -8 -4 + 4x + (6 + -5x) = 3(4x + -1) + -8 Reorder the terms: -4 + 6 + 4x + -5x = 3(4x + -1) + -8 Combine like terms: -4 + 6 = 2 2 + 4x + -5x = 3(4x + -1) + -8 Combine like terms: 4x + -5x = -1x 2 + -1x = 3(4x + -1) + -8 Reorder the terms: 2 + -1x = 3(-1 + 4x) + -8 2 + -1x = (-1 * 3 + 4x * 3) + -8 2 + -1x = (-3 + 12x) + -8 Reorder the terms: 2 + -1x = -3 + -8 + 12x Combine like terms: -3 + -8 = -11 2 + -1x = -11 + 12x Solving 2 + -1x = -11 + 12x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-12x' to each side of the equation. 2 + -1x + -12x = -11 + 12x + -12x Combine like terms: -1x + -12x = -13x 2 + -13x = -11 + 12x + -12x Combine like terms: 12x + -12x = 0 2 + -13x = -11 + 0 2 + -13x = -11 Add '-2' to each side of the equation. 2 + -2 + -13x = -11 + -2 Combine like terms: 2 + -2 = 0 0 + -13x = -11 + -2 -13x = -11 + -2 Combine like terms: -11 + -2 = -13 -13x = -13 Divide each side by '-13'. x = 1 Simplifying x = 1
| 5+a= | | 5x+6=109 | | x^2-15x=5950 | | 9-3(5x+4)=8 | | 5e^2x=75 | | 4/9x-7/6=-2 | | x+3=234 | | 9/8(x+7)=-2 | | 4/5x=-18 | | 3.8x=9(4)-9(x) | | t^2-14t+20=0 | | -8-2(1-a)=0 | | 2/3x+1/x=1/6 | | -4=5x-x | | t-21=-21 | | 6u=n | | 3x+4y=393 | | 4/37x+20/37=12/37 | | -7+2x=-1-(4-x) | | 5/47x+10/47=20/47 | | 225/17=-155/34+x | | 3(4x-12)=180 | | x=.45x+30 | | -8x-2/5=-9 | | x=.45x+40 | | 5/37x+25/37=15/37 | | 3/5x-6/7=12 | | 2(6x-2)-(9x-7)=8-(3x+2) | | 8x^2-56=0 | | 3(x-1)-1=15 | | -7x=-9 | | 6x=2x-16 |